Understanding climate injustice as social pathology through the lens of psychoanalysis, recognition theory and critical psychology - Bauriedl-Schmidt, Christine; Krimmer, Monika; Fellner, Markus; Cash, Paul (PINS-Psychology in Society, 2022)
The concept of climate injustice and a socio-critical, psychoanalytical perspective associate the climate crisis with other forms of social injustice classifying these as ‘social pathologies’. Two approaches towards social transformation, both recent Frankfurt School developments, are presented: (1) the double asymmetry of the social (Herrmann), a concept that sees the strength of social bonds as stemming from the acceptance of difference and (2) the value-oriented philosophical approach to radically change patterns of everyday life practice (von Redecker). The latter finds expression in social protest movements such as Fridays for Future or Extinction Rebellion. Seen through the lens of the anti-psychiatry movement, some ‘psychopathology’ can be re-framed as a meaningful, resistant expression of social grievances. Our integrative approach provides a framework that makes room for non-violent difference, destigmatisation of real (as opposed to neurotic) anxiety and the anger it produces, recognition of and responsibility for the other instead of bilateral subjugation, and mutual vulnerability as a driving force for change in both subjects and systems, on the road to healing social pathologies.